1973
DOI: 10.1111/j.1751-1097.1973.tb06450.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Flavins—i. Conventional and Laser Flash Photolysis Study of Alloxazine

Abstract: The photobleaching of alloxazine in buffered aqueous solution has been studied by means of flash photolysis using conventional and laser excitation sources. Several transient species have been characterized. The alloxazine triplet state (Amax 420 nm and 550 nm, T = 9 ps) was identified with the aid of low-temperature comparison experiments in ethanol. Transient absorption with A, .. 440 nm, which appears after decay of the triplet state, and whose second-order decay is pH-dependent, is postulated to be due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…The previously reported lifetimes of the triplet states are 12.0 ls for Lch12 and 9.4 ls for alloxazine in aqueous solution at pH 2.2,12 and 13 ls for alloxazine in ethanol. 28 The lifetimes reported by others correspond very well with those in Table 2. Triplet state quantum yields are also reported in Table 2 for the compounds studied.…”
Section: Spectroscopic and Photophysical Properties Of The Alloxazine...supporting
confidence: 83%
“…The previously reported lifetimes of the triplet states are 12.0 ls for Lch12 and 9.4 ls for alloxazine in aqueous solution at pH 2.2,12 and 13 ls for alloxazine in ethanol. 28 The lifetimes reported by others correspond very well with those in Table 2. Triplet state quantum yields are also reported in Table 2 for the compounds studied.…”
Section: Spectroscopic and Photophysical Properties Of The Alloxazine...supporting
confidence: 83%
“…dH do not yield alkoxyflavins upon illumination, neither in the presence, nor in the absence of RFloxH+ as potential sensitizer. Hence we are left with the choice of assuming nucleophilic photoaddition in an excited state RF1*oxH+ ; preliminary iodide quenching experiments point to the singlet state as the reactive species in agreement with the laser study by Dekker et al [2].…”
Section: The Photoreactive Speciwsupporting
confidence: 61%
“…The photoaddition reaction (Scheme 1) described in the present paper works only under acid condi- The neutral flavoquinone species Flo,H can, however, enter the same type of photoaddition a t pH 2 and 6, as demonstrated by Dekker et al [2] in a recent laser study. These authors were dealing with the parent compound alloxazine which is devoid of all the -CH, groups of the flavin species with which we are dealing and they find the excited singlet lAOxH* to be the photoreactant.…”
Section: The Photoreactive Speciwsupporting
confidence: 60%
“…For example, the possible products include: cation radicals, a semiquinone radical, a hydroxyalloxazine radical, anion radicals, dihydroalloxazine, hydroxyalloxazine, and the fully reduced form. 8,[27][28][29][30][31][32][33][34][35][36][37] For lumichrome in air-equilibrated water, Dekker et al 29 have also suggested the formation of a superoxide and singlet oxygen. The photochemistry on cellulose appears to be more specific, however, it is too early to conclude about the nature of the long-lived transient product or products.…”
Section: Discussionmentioning
confidence: 99%